Reconfigurable Instantaneous Frequency Measurement System Based on a Polarization Multiplexing Modulator - Chengwu Yang; Wenqi Yu; Jianguo Liu (IEEE Photonics Journal, 2019)
We propose and demonstrate a new reconfigurable instantaneous frequency measurement (IFM) system based on a dual-polarization dual-drive Mach–Zehnder modulator (DPol-DMZM). By simply adjusting the dc biases on both arms of the DPol-DMZM, the upper and lower bounds of the IFM measurement range can be independently adjusted. Experiments have shown that the lower frequency bound is as low as 2 GHz, and the upper frequency bound is up to 23 GHz. The resolution of the three frequency measurement bandwidths of 5, 6.5, and 8 GHz is less than ±0.2 GHz. It is noted that the proposed IFM system is power dependent. To solve this problem, a power-independent scheme with a similar system structure based on a dual-polarization dual-parallel Mach–Zehnder modulator is proposed and theoretically analyzed.